IMPLEMENTASI FSM (FINITE STATE MACHINE) PADA GAME MALIK LOOKS FOR THE HOLY BOOK - Adam Abiyu (JASTEN (Jurnal Aplikasi Sains Teknologi Nasional), 2023)
The development of the gaming industry has required developers tocreating a more immersive gaming experience. In this context,the use of Finite State Machines (FSM) has become a popular and effective solution inmanaging the storyline and more structured character development. This articleaims to review the basic concepts of FSM and describe its implementationin the game "Malik Looks for the Holy Book" as a means of education and entertainment.The application of FSM in this game aims to increase the dynamics of the gameas well as providing a clear structure in the player's journey. This abstract willdiscusses in detail the basic concepts of FSM applied in the game,highlighting how the use of FSM can improve the quality of the experienceplay for the players. Through analysis of the implementation of FSM in this game,this article presents a deeper understanding of how the framework worksFSM can be used to organize story lines, character behavior, and dynamicsthe game as a whole. Implementation of FSM in "Malik Looks for the HolyBook" has a positive impact in creating a fun gaming experiencestructured, dynamic and relevant to the expectations of modern players.